2017
DOI: 10.1007/s13197-017-2620-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the chemical composition, antioxidant and anti-inflammatory activities of distillate and residue fractions of sweet basil essential oil

Abstract: In this study, the chemical composition and antioxidant and anti-inflammatory activities of sweet basil ( L. Lamiaceae family) were evaluated. Sweet basil is a food-related plant that is widely used in traditional Chinese medicine. Sweet basil crude oil was processed via molecular distillation and further characterized using gas chromatography-mass spectrometry (GC-MS) to screen for new compounds. The GC-MS analysis identified thirty-eight compounds. The major constituents of the residue fraction were estragol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Many of the compounds identified in setubalense and murcott tangerines have been previously reported with a myriad of bioactivities. This includes antioxidant [ 17 , 18 , 19 , 20 ], anti-inflammatory [ 17 ], antidiabetic [ 19 , 21 ], antileishmanial [ 22 , 23 ], antimicrobial [ 19 , 22 , 24 , 25 ], cytotoxic [ 22 , 23 ], antitumor [ 26 ], and antiproliferative activities [ 27 , 28 ]. Furthermore, there are evidence pointing to other protective effects against Alzheimer’s [ 29 ] and tuberculosis [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many of the compounds identified in setubalense and murcott tangerines have been previously reported with a myriad of bioactivities. This includes antioxidant [ 17 , 18 , 19 , 20 ], anti-inflammatory [ 17 ], antidiabetic [ 19 , 21 ], antileishmanial [ 22 , 23 ], antimicrobial [ 19 , 22 , 24 , 25 ], cytotoxic [ 22 , 23 ], antitumor [ 26 ], and antiproliferative activities [ 27 , 28 ]. Furthermore, there are evidence pointing to other protective effects against Alzheimer’s [ 29 ] and tuberculosis [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, components of essential oils containing hydroxyl groups attached to the aromatic ring, unsaturations, and availability of electrons are associated with the antioxidant activity [ 39 ]. However, the essential oil of Tagetes lucida , which contains 95.7% of MC, produced IC 50 of 37.9 μ g/mL [ 40 ], while sweet basil essential oil (17.06% of MC) showed IC 50 of 1.092 ± 0.066 mg/mL [ 41 ]. Probably, this difference is related to compounds that may promote synergistic action among them [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aqueous extract of Ocimum gratissimum L. showed the capacity to reduce LPS-stimulated expression of BEAS-2B cell in human lung epithelial cells inhibiting its mRNA levels. Moreover, Li et al [122], investigating the action of distillate and residue fractions of basil essential oil (viz. estragole, methyl eugenol, linoleic acid, α-cadinol, and α-bergamotene) in-a Raw 264.7 cells line, have demonstrated that residue fractions prevents the expression of gene and suppressed the production of cytokines (TNF-a, IL-b, IL-6) in LPS-induced Raw264.7 cells, which contribute to treating various disorders caused by extreme oxidative stress.…”
Section: Cardiovascular Protectionmentioning
confidence: 99%